Impact of nonsurgical spinal decompression on paraspinal muscle morphology and mechanical properties in young adults with low back pain. Issue 7 (July 2020) - Lo, Wai Leung Ambrose; Lei, Di; Leng, Yan; Huang, Huanjie; Wang, Biru; Yu, Qiuhua; Li, Le
Objective: The mechanism underlying the benefit of nonsurgical spinal decompression (NSSD) on low back pain is unclear. This study was performed to investigate the immediate impact of NSSD on the mechanical properties and morphology of the paraspinal muscles. Methods: Participants with low back pain were recruited. NSSD therapy was provided on one occasion. A myotonometer was placed perpendicularly on the skin surface over the paraspinal muscle at the level of L3 /L4 to measure the mechanical muscle properties. The multifidus thickness was measured using B-mode ultrasound and defined as the distance between the transverse process and subcutaneous tissue fascia. The difference between before and after NSSD was analyzed by a paired t-test. Results: Thirty participants (mean age, 20.9 ± 0.8 years; 9 male, 21 female) were recruited. No significant difference was observed in the muscle mechanical properties or morphology between before and after the intervention. Conclusions: NSSD intervention did not induce immediate changes in the paraspinal muscle mechanical properties or multifidus thickness in young adults with low back pain. NSSD might produce benefits by stimulating mechanical receptors rather than inducing morphological changes or mechanical property alterations of the muscle fibers. These parameters may not be suitable outcome measures for NSSD intervention.